Screening Immunoactive Compounds of Ganoderma lucidum Spores by Mass Spectrometry Molecular Networking Combined With in vivo Zebrafish Assays - Li, Zhenhao; Shi, Yingqiu; Zhang, Xiaohui; Xu, Jing; Wang, Hanbo; Zhao, Lu; Wang, Yi (Frontiers in Pharmacology, 2020)
Ganoderma lucidum is a well-known herbal remedy widely used for treating various chronic diseases. Traditionally, the fruiting body is regarded as the medicinal part of this fungus, while recently, the therapeutic potentials of Ganoderma lucidum spore (GLS) is gaining increasing interests. However, detailed knowledge of chemical compositions and biological activities of the spore is still lacking. In this study, high-resolution mass spectrometry and molecular networking were employed for in-depth chemical profiling of GLS, sporoderm-broken GLS (BGLS) and sporoderm-removed GLS (RGLS), leading to the characterization of 109 constituents. The result also showed that RGLS contained more triterpenoids with much higher contents than BGLS and GLS. Moreover, the immunomodulatory activities of BGLS and RGLS were investigated in the zebrafish models of neutropenia or macrophage deficiency. RGLS exhibited more potent activities in alleviating vinorelbine-induced neutropenia or macrophage deficiency, and significantly enhanced phagocytic function of macrophages, which indicated the immunomodulatory activity of GLS was positively correlated with the content of triterpenoids. Further correlation analysis of chemical profiles of GLS and corresponding bioactivities by partial least squares regression identified the potential immunoactive compounds of GLS, including 20-hydroxylganoderic acid G, elfvingic acid A and ganohainanic acid C. Our findings suggest that combining mass spectrometry molecular networking with zebrafish-based bioassays and chemometrics is a feasible strategy to reveal complex chemical compositions of herbal medicines, as well as to discover their potential active constituents.